The evaluation on the transformation of technical education faculties into faculties of technology according to the Delphi technique - Tuncer, Murat; Tanas, Ramazan (Deomed Publ, Istanbul, 2015)
In the study, it has been planned to investigate the transformation of technical education faculties into technology faculties by employing the method of Delphi. For this purpose, opinions of teaching staff regarding how vocational schools will be affected, employability of students after graduation, how teaching staff were affected, content, structure and functioning of the courses, applications of the courses, postgraduate education, comparability with the EU countries, students preferring these faculties and qualifications of those graduated from these schools were received and evaluated. The data collection process of the research was conducted on the basis of Delphi technique. The population of the study can be expressed as faculty members working in the Technical Education and Technology faculties in Turkey. The sample of the study consists of faculty members in technology faculties and technical education faculties of seven universities (Firat, Marmara, Gazi, Afyon Kocatepe, Karabuk, Suleyman Demirel and Sakarya Universities) which have started enrollments for these majors during the period of the research. In accordance with the opinions of the faculty members, considering the findings obtained in this study; it has been seen that they think vocational schools would be affected in a negative way, the chance of students graduated from these vocational schools to be a teacher in their fields were reduced. One another finding of the research is that faculty members are not very sure about whether the employment rate of those graduated from technology faculties is higher.
Keywords: Delphi method; program evaluation; technical education faculties; vocational education